2017
DOI: 10.3390/su9050834
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Training Satisfaction and the Readiness to Transfer Learning: The Mediating Role of Normative Commitment

Abstract: Abstract:Organizations are becoming increasingly demanding in regard to training cost rationalization and justification, and to the associated result achievement obligation. In practice, these pressures result in the introduction of more or less adequate efficiency indicators in relation to training programs. The goal of this study is to understand the relationship between training and training efficiency indicators at the individual level, using a mediation model. This study proposes a three-factor mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…Participants expressed an overall appreciation of the program, a desire to receive information in order to participate in upcoming events and reported that they were eager to share the information obtained with their peers. These results support the link between satisfaction, sense of belonging (in this case, to the cross-training programme), and a readiness to transfer learning (Ben Mansour, Naji, & Leclerc, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Participants expressed an overall appreciation of the program, a desire to receive information in order to participate in upcoming events and reported that they were eager to share the information obtained with their peers. These results support the link between satisfaction, sense of belonging (in this case, to the cross-training programme), and a readiness to transfer learning (Ben Mansour, Naji, & Leclerc, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Job training satisfaction is the extent to which people like or dislike the set of planned activities or dislike the set of planned activities organized to develop the knowledge, skills, and attitudes required to effectively a given tasks or job" ( [32], p. 483). According to Schmidt, the definition of job training satisfaction has several key components [100]. First, the focus of evaluation is on-the-job training as a whole, rather than on a single part of training activities such as a training course, trainers, facilities, or training content.…”
Section: Job Training Satisfaction 41 the Definition Of Job Trainingmentioning
confidence: 99%
“…The research results have also indicated that the relationship between job training satisfaction Job Training Satisfaction, Job Satisfaction, and Job Performance DOI: http://dx.doi.org /10.5772/intechopen.89117 and turnover intentions can be mediated by job satisfaction. Mansour et al showed that there is a positive relation between job training satisfaction and normative commitment [100]. Moreover, job training satisfaction was found to be positively related to organizational citizenship behavior [104,105], organizational commitment (OC), and job involvement (JI) [105].…”
Section: The Relationship Between Job Training Satisfaction Job Satimentioning
confidence: 99%
“…The PI and the WR measures focused on knowledge, ability, and willingness to use WR, and results showed that the intervention improved the perceived utility of such resources. The improved perception of the workplace is noteworthy as the actual impact of training may depend on how much employees feel their organization cares about them [ 62 ].…”
Section: Discussionmentioning
confidence: 99%